2022
DOI: 10.7759/cureus.30787
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ashwagandha (Withania somnifera) Root Extract for Improvement of Sexual Health in Healthy Women: A Prospective, Randomized, Placebo-Controlled Study

Abstract: BackgroundPoor sexual function is a widespread problem affecting about 40% of women and this may worsen their quality of life. Ashwagandha (Withania somnifera) an adaptogenic herb has been reported to improve sexual satisfaction, sleep, and quality of life in women. ObjectiveThe purpose of the study was to evaluate the efficacy and safety of standardized Ashwagandha root extract in improving sexual function in healthy females. MethodsIn this prospective, randomized, placebo-controlled study, 80 women between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…It reduces the level of cortisol in blood serum in patients with chronic stress, restores the functions of the adrenal glands and normalizes the sympathetic nervous system [72]. Animal studies have confirmed the effect of Withania somnifera on the production of sex hormones, as evidenced by its effect on LH, FSH, testosterone and progesterone [71,72,73]. Plant phytochemicals in combination with drugs or other clinical treatments can be used for therapeutic purposes, including the treatment of SARS-CoV-2 infection [74].…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…It reduces the level of cortisol in blood serum in patients with chronic stress, restores the functions of the adrenal glands and normalizes the sympathetic nervous system [72]. Animal studies have confirmed the effect of Withania somnifera on the production of sex hormones, as evidenced by its effect on LH, FSH, testosterone and progesterone [71,72,73]. Plant phytochemicals in combination with drugs or other clinical treatments can be used for therapeutic purposes, including the treatment of SARS-CoV-2 infection [74].…”
Section: Methodsmentioning
confidence: 88%
“…Withania somnifera a extract has a calming, anti-inflammatory, adaptogenic, cognitive, antitumor, antioxidant, antibacterial, immunomodulatory effect, normalizes the sleep cycle, and improves female sexual health [70,71]. Withania somnifera is considered an «adaptogen» because it protects the body from stress and helps the body recover from the effects of stress.…”
Section: Methodsmentioning
confidence: 99%
“…There was a greater improvement in FSDS scores with Ashwagandha compared to placebo. More women with Ashwagandha reported improvements in satisfying sexual encounters (SSEs) at week 4 and week 8 compared to placebo [14].…”
Section: Ashwagandha's Impact On the Reproductive Systemmentioning
confidence: 99%
“…Also, Ashwagandha's influence on the hormonal system deserves attention. It has been proved that it modulates pituitary functions [12], can improve thyroid gland homeostasis [13], regulates adrenal activity and has a multidirectional influence on the reproductive system [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that herbs enhance sexual potency and remedy fertility problems. For instance, Ashwagandha, 12 Pomegranate, 13 Cinnamon, 14 Dates, 15 Maca Root, 16 etc, 17 , 18 are herbal medicines still traditionally used as sexual enhancers in the Middle East and East Asia. 18 , 19 However, no reliable academic evidence is available regarding the effects of the majority of these plans and their mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%